An Analysis on IL Fossilization Phenomenon in Students Writing Performance - Nurul Aini Aini; Muhammad Khoirul Mufid; Eny Maulita Purnama Sari (EDUVELOP, 2020)
This present study tries to investigate the students’ writing performance to know whether interlanguage fossilization is occurs or not. The primary goal of this research is to give information relating interlanguage fossilization in students’ writing performance of English Education Study Program of IAIN Jurai Siwo Metro. This research is qualitative research. It is used to describe interlanguage fossilization that occurred in students’ writing performance. The writer uses observation, documentation and interview to collect the data. Purposive sampling is the technique for choosing the ten students of the sixth and the eight semester of English Education Study Program of IAIN Jurai Siwo Metro in the Academic Year of 2017/2018. The result of this research shows that there are two types of interlanguage fossilization that are commonly produced by students’ writing performance. They are syntactical fossilization and morphological fossilization. Syntactical fossilization consists of 71, 86% and morphological fossilization consists of 28, 14%. Moreover, interlanguage fossilization phenomenon in students’ writing performance is caused by the students’ low English proficiency. Therefore, the students should be more active to improve their English ability.